Cultural populism in the Uuno Turhapuro films of the 1990s - Kallioniemi Noora (United Kingdom, 2025)
This article examines the cultural meanings given to the comedy character Uuno Turhapuro, in particular during the early 1990s. Focusing on two films, Uuno Turhapuro herra Helsingin herra (‘Uuno Turhapuro, Mr Bigwig of Helsinki’) (1991) and Uuno Turhapuro Suomen tasavallan herra presidentti (‘Uuno Turhapuro, Mr President of the Republic of Finland’) (1992), I discuss the way this unemployed, idle but resourceful character belongs to the tradition of Finnish audio-visual popular culture and analyse the cultural populism related to the authorship of Pertti ‘Spede’ Pasanen. The figure of Uuno is also a presidential parody that reflects the changing attitude in Finland towards those in power after the long administration of President Urho Kekkonen. As a historian, I have endeavoured to illustrate the ways comedy relates to the time period in which it was made.